2004
DOI: 10.1111/j.1467-7652.2004.00104.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictable activation of tissue‐specific expression from a single gene locus using the pOp/LhG4 transactivation system in Arabidopsis

Abstract: SummaryThe pOp / LhG4 transcription factor system was used to determine whether the synthetic pOp promoter, integrated at one position in the Arabidopsis genome, could be efficiently and faithfully activated by the heterologous transcription factor, LhG4, expressed in a variety of different patterns. This is a precondition for the development and exploitation of large collections of LhG4 activation lines that direct predictable tissue-specific expression of transgenes. We selected a pOp-GUS reporter insertion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
46
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 65 publications
(129 reference statements)
0
46
0
Order By: Relevance
“…These results demonstrate that the system can be used to generate a library of tissuespecific transactivator plant lines for the activation of LexA responder T-DNAs and that the genomic location of the activator or responder is equally likely to affect the reliability of the system. Such efficiency could not be easily achieved using systems in which gene expression is more sensitive to the position of the responder T-DNA (Baroux et al, 2005). In the system described by Baroux et al (2005), a similar percentage of plant lines (to data presented here) showed transactivated GUS expression (i.e.…”
Section: Discussion Local Inducible Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results demonstrate that the system can be used to generate a library of tissuespecific transactivator plant lines for the activation of LexA responder T-DNAs and that the genomic location of the activator or responder is equally likely to affect the reliability of the system. Such efficiency could not be easily achieved using systems in which gene expression is more sensitive to the position of the responder T-DNA (Baroux et al, 2005). In the system described by Baroux et al (2005), a similar percentage of plant lines (to data presented here) showed transactivated GUS expression (i.e.…”
Section: Discussion Local Inducible Expressionmentioning
confidence: 99%
“…Such efficiency could not be easily achieved using systems in which gene expression is more sensitive to the position of the responder T-DNA (Baroux et al, 2005). In the system described by Baroux et al (2005), a similar percentage of plant lines (to data presented here) showed transactivated GUS expression (i.e. 86% of plant lines with GUS responders inserted at 37 independent loci), but expression was often weak (e.g.…”
Section: Discussion Local Inducible Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 In particular, the mis-expression of genes that cause lethality or strong pleiotropic effects cannot be accomplished through activation tagging. 6 Another concern of activation tagging is whether the gain-of-function phenotype of a mutant reflects the normal biological role of a gene. Notably, the CaMV 35S enhancers can lead to enhancement of endogenous gene expression and the resultant phenotype, as opposed to ectopic overexpression or mis-expression driven by native promoters, which would be more likely to reflect the normal role of the activated gene.…”
Section: Tissue-and Organ-specific Promoter-driven Gene Expressionmentioning
confidence: 99%
“…These technologies can be implemented easily for a single gene using specific constructs that direct its down or upregulation under constitutive, tissue-specific or inducible conditions. 6 Developmental processes and differentiation of distinct cell types depend on the regulation of gene expression in space and time. Most systems that manipulate gene expression allow control in one dimension, space or time.…”
Section: Tissue-and Organ-specific Promoter-driven Gene Expressionmentioning
confidence: 99%